PODCAST-MEDIATED LISTENING INSTRUCTION IN EFL CLASSROOMS: EVIDENCE FROM BBC LEARNING ENGLISH IN INDONESIA - Dita Aprida; Huriyah; Edy Waloyo (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2026)
This  study  aimed  to  investigate  the  effect  of  BBC  Learning  English  podcasts  on  students’  listening  comprehension  in  English  as  a  Foreign  Language  (EFL)  classrooms.  The  research  employed  a  quantitative  approach  using  a  quasi-experimental  design  involving  an  experimental  class  and  a  control  class  at  one  public  junior  high  school  in  Cirebon  during  the  2025/2026  academic  year.  The  participants  were  eighth-grade  students  categorized  as  intermediate  EFL  learners.  The  data  were  collected  through  pre-test  and  post-test  listening  comprehension  tests  to  measure  students’  ability  in  understanding  spoken  English.  The  experimental  class  received  listening  instruction  using  BBC  Learning  English  podcasts,  while  the  control  class  was  taught  using  conventional  textbook-based  listening  materials.  The  findings  showed  that  the  mean  score  of  the  experimental  class  increased  from  42.58  to  66.77,  whereas  the  control  class  improved  from  42.78  to  54.81.  Furthermore,  the  independent  samples  t-test  revealed  a  significance  value  of  0.007,  which  was  lower  than  0.05,  indicating  a  significant  difference  between  both  groups.  The  study  concludes  that  BBC  Learning  English  podcasts  had  a  positive  and  significant  effect  on  students’  listening  comprehension.  Therefore,  BBC  Learning  English  podcasts  can  be  used  as  an  effective  and  meaningful  listening  learning  resource  for  intermediate  EFL  students.